One-year periodization of training loads of Russian and Norwegian elite cross-country skiers - Myakinchenko, E. B.; Kriuchkov, A. S.; Adodin, N. V.; Dikunets, M. A.; Shestakov, M. P. (Journal of Human Sport & Exercise, 2021)
The study intended to compare the training load volume (TrV) distribution of elite Russian (RuXC) and Norwegian (NorXC) cross-country skiers in a one-year macrocycle. Daily TrV of 11 RuXC skiers averaged for the period 2014/15-2017/18. The NorXC skiers` TrV obtained from the study by Sandbakk (2017). RuXC skiers had a lower volume of low-intensity (LIT, below aerobic threshold) and high-intensity (HIT, above anaerobic threshold) endurance training. They used a "pyramidal" model of intensity ratio during the entire macrocycle and did not decrease the volume of moderate-intensity (MIT) endurance training in competition periods (CPs). Conversely, NorXC skiers followed the "pyramidal" model of intensity in the preparation period (PP) but the "polarized" model in CP, significantly reducing the volume of MIT and increasing that of HIT. RuXC skiers increased TrVs more rapidly at the beginning of PPs, achieving TrV peak in June, and then gradually decreased them by March. NorXC skiers increased TrVs gradually by July and then maintained this approximate volume until November. RuXC skiers had peak volumes of LIT and strength training simultaneously in June; NorXC skiers engaged in large amounts of strength training in May and June until reaching maximum endurance loads. RuXC skiers had two "blocks" of strength training; NorXC skiers had three. A comparative analysis of the TrV distributions among the RuXC and NorXC skiers revealed significant similarity. Therefore, they can consider as models of the modern annual periodization of training loads for this kind of sport.